2019
DOI: 10.1177/1533033819830748
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Thyroid Nodules in Ultrasound Images Using Direction-Independent Features Extracted by Two-Threshold Binary Decomposition

Abstract: In recent years, several computer-aided diagnosis systems emerged for the diagnosis of thyroid gland disorders using ultrasound imaging. These systems based on machine learning algorithms may offer a second opinion to radiologists by evaluating a malignancy risk of thyroid tissue, thus increasing the overall diagnostic accuracy of ultrasound imaging. Although current computer-aided diagnosis systems exhibit promising results, their use in clinical practice is limited. One of the main limitations is that the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Of these, seven analyzed the performance of various statistical textural features [33,34,35,36,37,38,39], while six studies analyzed performance of a combination of textural features and other features, namely texture and wavelet transform features [40,41,42], texture and morphological features [43], and texture and radiological features [44], as well as texture analysis, elastography and grey scale ultrasound [45]. Two studies evaluated the performance of the combination of histogram and fractal texture analysis for support vector machine (SVM) and random forest classifiers [46,47] and one study assessed the accuracy of wavelet texture analysis for different classifiers [48]. Three studies focused on artificial intelligence texture analysis; two evaluated the diagnostic performance of the combination of artificial neural network (ANN) textural analysis with SVM [49], and ANN with binary logistic regression analysis [50], while another evaluated deep learning convolutional neural network feature classification performance using a random forest classifier [51].…”
Section: Resultsmentioning
confidence: 99%
“…Of these, seven analyzed the performance of various statistical textural features [33,34,35,36,37,38,39], while six studies analyzed performance of a combination of textural features and other features, namely texture and wavelet transform features [40,41,42], texture and morphological features [43], and texture and radiological features [44], as well as texture analysis, elastography and grey scale ultrasound [45]. Two studies evaluated the performance of the combination of histogram and fractal texture analysis for support vector machine (SVM) and random forest classifiers [46,47] and one study assessed the accuracy of wavelet texture analysis for different classifiers [48]. Three studies focused on artificial intelligence texture analysis; two evaluated the diagnostic performance of the combination of artificial neural network (ANN) textural analysis with SVM [49], and ANN with binary logistic regression analysis [50], while another evaluated deep learning convolutional neural network feature classification performance using a random forest classifier [51].…”
Section: Resultsmentioning
confidence: 99%
“…In the work by Chang et al [22], the support vector machines classifier showed a diagnostic accuracy reaching up to 98.3% for 59 nodules. A recent work by Prochazka et al [38] employed a random forest and support vector machine classifier for evaluating segmentation-based fractal texture analysis, and the authors achieved a diagnostic accuracy of 94.3% with their model. Although all studies mentioned above have yielded promising results, the use of a small sample size in ML-based diagnostic models will undoubtedly introduce bias and variance [39].…”
Section: Discussionmentioning
confidence: 99%
“…In their review, Acharya et al [9] claimed that ML classifiers using non-clinical features showed higher classification accuracies than were obtained by radiologists using clinical features, and also presented the following additional advantages of using non-clinical features: (1) such features can be automatically extracted from US images and quantified as numerical values that can be used for automated classification; (2) there is no need for visual inspection and interpretation, and therefore, the results are more objective; and (3) such CAD systems can be written as software applications at a low cost and installed on existing computers in clinics at no extra cost. The accuracy of ML classifiers for thyroid nodule classification in recently published studies is shown in Table 1 [121314151617].…”
Section: Imaging Analysis Using Ai/mlmentioning
confidence: 99%
“…Reproduced from Prochazka et al [17]. DWT, discrete wavelet transform; CEUS, contrast-enhanced ultrasonography; kNN, k-nearest neighbor; SVM, support vector machine; HRUS, high-resolution ultrasound; SFTA, segmentation-based fractal texture analysis; RF, random forest.…”
Section: Figmentioning
confidence: 99%